Stabilization of phosphofructokinase 1 platelet isoform by AKT promotes tumorigenesis. Issue 1 (December 2017) - Lee, Jong-Ho; Liu, Rui; Li, Jing; Zhang, Chuanbao; Wang, Yugang; Cai, Qingsong; Qian, Xu; Xia, Yan; Zheng, Yanhua; Piao, Yuji; Chen, Qianming; Groot, John; et al.
Abstract Phosphofructokinase 1 (PFK1) plays a critical role in glycolysis; however, its role and regulation in tumorigenesis are not well understood. Here, we demonstrate that PFK1 platelet isoform (PFKP) is the predominant PFK1 isoform in human glioblastoma cells and its expression correlates with total PFK activity. We show that PFKP is overexpressed in human glioblastoma specimens due to an increased stability, which is induced by AKT activation resulting from phosphatase and tensin homologue (PTEN) loss and EGFR-dependent PI3K activation. AKT binds to and phosphorylates PFKP at S386, and this phosphorylation inhibits the binding of TRIM21 E3 ligase to PFKP and the subsequent TRIM21-mediated polyubiquitylation and degradation of PFKP. PFKP S386 phosphorylation increases PFKP expression and promotes aerobic glycolysis, cell proliferation, and brain tumor growth. In addition, S386 phosphorylation in human glioblastoma specimens positively correlates with PFKP expression, AKT S473 phosphorylation, and poor prognosis. These findings underscore the potential role and regulation of PFKP in human glioblastoma development. Phosphofructokinase 1 (PFK1) plays a critical role in glycolysis. Here the authors show that PFK1 platelet isoform is upregulated in Glioblastoma and is required for tumor growth mechanistically, such upregulation is due to an increased stability induced by AKT activation via phosphorylation on residue S386.